Risk-adapted therapy for young children with medulloblastoma (SJYC07): therapeutic and molecular outcomes from a multicentre, phase 2 trial - Robinson, Giles W.; Korbel, Jan Oliver; Jones, David T. W.; Lichter, Peter; Kool, Marcel; Pfister, Stefan (The lancet. Oncology, 2018)
Background - Young children with medulloblastoma have a poor overall survival compared with older children, due to use of radiation-sparing therapy in young children. Radiotherapy is omitted or reduced in these young patients to spare them from debilitating long-term side-effects. We aimed to estimate event-free survival and define the molecular characteristics associated with progression-free survival in young patients with medulloblastoma using a risk-stratified treatment strategy designed to defer, reduce, or delay radiation exposure. -
Gesehen am 14.04.2020